Quantitative phase Analysis: It's role in characterization of Spheroidal graphite Iron. (2020) - Bramaramba, V.; Behera, R.K.; Saurabh, Sushant; Sen, S.
Abstract: The purpose of the work was to study the structure property correlation of Spheroidal Graphite Iron (S.G.Iron). With this end in view differently heat treated specimens of two different grades of S.G. Iron was studied. After developing the microstructure of all of them quantitative phase analysis was performed with the help of image-analyser. Efforts were made to determine whether a relationship between the amount of different phases and mechanical properties (mainly toughness) could be established. For this purpose mechanical properties were evaluated for all the heat treated specimens and efforts were made to determine relationship between mechanical properties and proportion of soft phases.